Proceeding of the 12th European Conference on e-Government, ESADE Ramon Llull University Barcelona, Spain, 14-15 June 2012 - (12th : 2012 : Barcelona, Spain); Gasco, Mila (Reading : Academic Publishing International Limited, 2012)
PSZKLL